RAGAM BAHASA INDONESIA DALAM KOMUNIKASI POLITIK - Sitti Rabiah (Magister Ilmu Politik Universitas Hasanuddin, 2016)
Indonesian language as the part of the Indonesian struggle for independence through the Sumpah Pemuda in 1928 confirmed the Indonesian language as the national language and unifying language of various races, religions and ethnicities. Post-independence, the Indonesian language strengthen its presence as a